Carbothermic reduction synthesis of calcium hexaboride using PVA-calcium hexaborate mixed gels. Issue 3 (15th February 2018) - Yilmaz, Duygu; Savaci, Umut; Koç, Nurşen; Turan, Servet
Abstract: In this study, PVA-CaB6 O10 ·5H2 O precursor mixtures were prepared by coating the ceramic powders with PVA to synthesize CaB6 via carbothermal reduction. Boron loss, the main problem in the synthesis of borides, was reduced by the use of metastable CaB6 O10 as a transitional phase which is stable until the critical temperature ranges where the boron sub-oxides have higher volatilities. To minimize boron loss, due to the high hydrophilicity and ability to form cross-linked PVA-borate gels, PVA was used as a carbon source and carbon coating process was carried out via pyrolysis of the PVA - CaB6 O10 ·5H2 O mixed gels. The effect of the molecular weight of PVA on the CaB6 synthesis was also studied. Because of highly efficient interaction of CaB6 O10 ·5H2 O with the PVA60-water solution, PVA60 was found to be the optimal carbon source. The CaB6 O10 ·5H2 O-PVA60 composite powder was characterized by using Fourier transform infrared spectroscopy (FTIR) and the effect of molecular weight of the PVA's on the thermal characteristics of mixed powders were analyzed by using simultaneous thermal analysis (STA). The effect of carbothermic reduction temperature and dwell time on the phase formation were examined via x-ray diffractometer (XRD) and scanning and transmission electron microscopy (SEM and TEM) techniques. The optimum synthesis conditions were determined for the formation of CaB6 as 1450ºC for 12 h under an Argon flow by using the CaB6 O10 ·5H2 O-PVA60 mixed precursor.